Strategy for the Implementation of Blended Learning at MTs Muhammadiyah 1 Taman - Shafa Ayu Faramida; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This research is about what learning strategies were used during the Covid-19 pandemic at MTS Muhammadiyah 1 Taman. The Covid-19 pandemic has disrupted the conventional learning process. With that, this research was conducted to determine the learning strategies carried out at the school. This research use desciptive qualitative approach. The purpose of the research was to obtain an overview of the implementation of online learning at MTS Muhammadiyah 1 Taman as an effort to reduce the spread of the Covid-19 virus. The data source used is the primary data source. he informant in this is the Principal of Madrasah Mts Muhammadiyah 1 Taman. Data collection techniques used include interviews, observation, and documentation. The results of this study indicate that the learning strategy during the Covid-19 pandemic uses the Blendid Learning strategy which is carried out face-to-face and online. With this strategy, students can enter school on a predetermined schedule in turn. This strategy is very efficient because in addition to students being able to do face-to-face learning with the teacher in the classroom, they can also access the material provided online wherever they are. When students do not understand the material provided, they can discuss it in person in class or online. Of course, this is very beneficial for both educators and students, because learning will be very comfortable and more effective.